If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 + -1 + 3 + 4x = 14 Reorder the terms: 5 + -1 + 3 + 3x + 4x = 14 Combine like terms: 5 + -1 = 4 4 + 3 + 3x + 4x = 14 Combine like terms: 4 + 3 = 7 7 + 3x + 4x = 14 Combine like terms: 3x + 4x = 7x 7 + 7x = 14 Solving 7 + 7x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 7x = 14 + -7 Combine like terms: 7 + -7 = 0 0 + 7x = 14 + -7 7x = 14 + -7 Combine like terms: 14 + -7 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| (x+3)(x+1)=0 | | 17x=180 | | 10=-2c | | 6(5x+4)(3x-1)=0 | | v+42-3v=-34 | | 9g+8g=17 | | 8[5-3]=0 | | 3[2a-4]=0 | | 2c+a=-3c+44 | | 2z+5+3z=10 | | -5x^2+15x-9=0 | | -3[r+4]=21 | | -5w(w-3)(w+2)=0 | | -3[r+4]=-21 | | 5[q+6]=-20 | | 5[q+6]=20 | | 8x-9=33-4x | | 5x+7=2x-9 | | -3(-4-6x)=84 | | x^3+2x^2+4=0 | | -y+3z=9 | | 12+18x=84 | | 2+18x=84 | | 6x-6x=-2 | | 3x^3-6x^2-45x=0 | | 7k^2+6k-1=0 | | 5-(3n+5)=3-(7n+3) | | 14m+4n-6m+11n= | | 6n^2-14+8=0 | | 3(u-3)=2(x+5) | | [b+5]=2b+3 | | 15x^2-61x+53=-3 |